Sistem Informasi Berbasis Web Penyewaan Wedding Organizer pada Doni Organizer - Wijaya, Lalu Kerta; Septiana, Rina; Alimuddin, Alimuddin (Infotek : Jurnal Informatika dan Teknologi, 2021)
In carrying out and celebrating the wedding party, each couple will make total preparations to face this sacred event, especially with the various customary and cultural backgrounds of each partner, of course they have different habits in carrying out and celebrating the wedding party. This of course can be a continuous business opportunity that can be developed over time. In planning and supervising the implementation of a series of wedding ceremony events according to a predetermined schedule and budget, an application is needed that can be used to make it easier for customers. Wedding Organizer is a service that functions personally to assist the bride and groom and their families in planning and supervising the implementation of a series of wedding events according to a predetermined schedule and budget. The Wedding Organizer rental information system at Doni Organizer is made by utilizing web-based information technology, with the aim of expanding the area of promotion and sale of wedding packages and simplifying ordering and helping with their wedding planning problems. The Wedding Organizer rental information system at Doni Organizer uses the PHP and MySQL programming languages.